Sintilimab combined with chemotherapy in advanced pulmonary epithelioid hemangioendothelioma: a case report and translational insights - Jing, Lijun; An, Huiyun; Yang, Hao; Zhang, Liming; Li, Tongyuan; Wang, Yongming (Frontiers in Oncology, 2025)
BackgroundPulmonary epithelioid hemangioendothelioma (PEH) is an exceedingly rare vascular tumor, presenting a significant challenge due to its limited treatment options. Immunotherapy in combination with chemotherapy emerges as a potential frontier, yet the understanding of its application in PEH remains in its infancy.MethodsA male patient initially faced misdiagnosis as having aspergillosis. Through histopathology and immunohistochemistry, a definitive diagnosis of PEH was later established. The treatment journey involved surgical resection, followed by chemotherapy with albumin-bound paclitaxel and carboplatin, and finally immunotherapy with sintilimab.ResultsA remarkable radiological improvement was observed post-sintilimab administration, leading to disease stabilization. Significantly, this is the first-ever report of the efficacy of sintilimab in PD-L1-high PEH, filling a critical gap in the existing literature.ConclusionThis case not only underscores the potential of sintilimab in PD-L1-high PEH but also sets a precedent for further exploration of immune checkpoint inhibitors in this rare disease.